Most Probable Number (MPN) Coliform of Jamu Gendong Beras Kencur in Traditional Markets in Sukoharjo Region - Makhabbah Jamilatun; Pradea Indah Lukito; Eka Nanda Safitri (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
: One of the traditional medicines that is very popular with the public is the jamu gendong beras kencur. The safety of traditional medicine products (herbal medicine) is a demand that has been put forward since the emergence of human health problems due to microorganism contamination, such as coliform. This study aims to determine Coliform bacteria contamination in jamu gendong beras kencur in traditional markets in the Sukoharjo area. The method used in this study is the MPN (Most Probable Number) method, which consists of two stages, namely the Presumptive Test and the Confirmed Test. The study results showed that samples with codes 1, 2, 5, 6, 7, 8, 11, and 12 had an MPN value of 0/100 ml. Furthermore, samples with codes 3, 4, 9, and 10 showed an MPN value >0/100 ml. Based on the research results, samples that meet the quality of good drinking water based on the Regulation of the Minister of Health of the Republic of Indonesia in 2010, are samples with codes 1, 2, 5, 6, 7, 8, 11, 12 while samples with codes 3, 4, 9, 10 do not meet the requirements. There needs to be education on how to make good herbal medicine, environmental sanitation, and clean herbal medicine sales locations so that herbal medicine sellers can improve the quality of the herbal medicine they sell and ensure it is safe to consume